Investigating the Lived Experience of People with Down Syndrome with Dementia: Overcoming Methodological and Ethical Challenges. Issue 2 (June 2016) - Watchman, Karen
Abstract: Adults with Down syndrome are at increased risk of dementia at a significantly younger age and remain under‐represented as participants in dementia‐related research. Because little is known about their personal experiences either immediately postdiagnosis or as dementia progresses, there is little opportunity that shared individual experiences can shape future policy and practice. To remedy this omission, the author examined methodological and ethical challenges identified as part of a research study that included people with Down syndrome affected by dementia. It has been contended that traditional qualitative approaches are less effective when participants are affected by changing cognitive functioning and reduced verbal communication. To counteract this contention overt participant observation and an adapted narrative research method were used as part of a three‐year longitudinal study to help better understand the lived experiences of three adults with Down syndrome affected by dementia. Methodological and ethical challenges were shown to collide, and factors contributing to this effect included identifying process consent, accurate representation of participants, the role of and relationship with the researcher, participants, lack of awareness of their diagnosis of dementia, and need to recognize the importance of social interaction while maintaining academic rigor. Reflections are proffered on two conceptual and practice issues, with a call for both to be recognized and addressed in terms of future policy and practice. First is a lack of awareness of a sense of "self" or identity, resulting in individuals with Down syndrome and dementia being defined by their situation rather than individual preference or need. Second is the lack of information postdiagnosis about dementia being shared with people who have Down syndrome.